Calculating effective growth rate from a random Leslie model: Application to incidental mortality analysis - Caceres Garcia Faure, Manuel Osvaldo; Cáceres Saez, Iris (Elsevier Science, 2013)
Fil: Caceres Garcia Faure, Manuel Osvaldo. Universidad Nacional de Cuyo; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Area de Energía Nuclear. Instituto Balseiro; Argentina